Anisotropic Composites of Desaminotyrosine and Desaminotyrosyl Tyrosine Functionalized Gelatin and Bioactive Glass Microparticles. Issue 1718 (2015) - Julich-Gruner, Konstanze K.; Lendlein, Andreas; Boccaccini, Aldo R.; Neffe, Axel T.
ABSTRACT: Functionalization of gelatin with desaminotyrosine (DAT) and desamino tyrosyl tyrosine (DATT) has been demonstrated to allow network formation based on non-covalent interactions of the aromatic moieties. Based on the observation that the DAT(T) groups furthermore could interact with hydroxyapatite fillers, here it was investigated whether such interactions of DAT(T) could also be employed to stabilize composites formed by functionalized gelatins and bioactive glass (BG) particles. Because of sedimentation of the BG microparticles during the gelification, anisotropic composites with two distinct layers were formed. The characterization of mechanical properties by tensile tests and rheology showed that all composites of non-functionalized and DAT(T) functionalized gelatins with BG microparticles showed an increased Young's modulus ( E ) up to 3 MPa, an increased storage modulus ( G ') up to 100 kPa, increased tensile strength ( σ max ) up to 3.4 MPa, and increased loss modulus ( G '') compared to the pure matrices. As the observed effects were more pronounced in the DAT(T) functionalized gelatins compared to non-functionalized gelatins, and a much increased thermal stability of these composites was found, it is likely that there are binding interactions between the aromatic moieties and the BG microparticles. This effect open opportunities for the further development of this type of gelatin-based composites for bone regeneration applications.